2002
DOI: 10.1080/09540120220097964
|View full text |Cite
|
Sign up to set email alerts
|

The role of prisons in the HIV epidemic among female injecting drug users

Abstract: The objective of this study was to describe factors associated with imprisonment of female injecting drug users (IDUs) and to assess if female IDUs who have been in prison have different HIV risk behaviours when compared to females IDUs who have never been incarcerated. A seroepidemiological survey was conducted of 304 female IDUs recruited in outreach and treatment programmes in Madrid, Spain. Data on sociodemographic characteristics and recent and lifetime risk factors, sexual and reproductive history and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Transmission risks may be magnified within prisons and jails because of the prevalence of high-risk sexual behaviors and sharing of injection equipment, in part due to the lack of access to condoms or sterile injection equipment (Estébanez et al, 2002;Frank, 1999;Hammett et al, 1999;Mahon 1996;Mutter et al, 1994). Although many offenders may be aware of their HIV status, numerous studies have reported that even among individuals who are informed of their HIV test results, most continue to engage in high-risk sexual activity (Belenko et al, 2004;Cleary et al, 1991;Ickovics et al, 1994;Kalichman et al, 1997;Landis et al, 1992).…”
Section: Introductionmentioning
confidence: 91%
“…Transmission risks may be magnified within prisons and jails because of the prevalence of high-risk sexual behaviors and sharing of injection equipment, in part due to the lack of access to condoms or sterile injection equipment (Estébanez et al, 2002;Frank, 1999;Hammett et al, 1999;Mahon 1996;Mutter et al, 1994). Although many offenders may be aware of their HIV status, numerous studies have reported that even among individuals who are informed of their HIV test results, most continue to engage in high-risk sexual activity (Belenko et al, 2004;Cleary et al, 1991;Ickovics et al, 1994;Kalichman et al, 1997;Landis et al, 1992).…”
Section: Introductionmentioning
confidence: 91%
“…A history of incarceration is a particularly significant risk factor for HIV (Buavirat et al, 2003;Estébanez et al, 2002;Robles et al, 1993), as a result of unsafe drug injection and unsafe sex in jail/prison (Buavirat et al, 2003;Clarke et al, 2001;Estébanez et al, 2002;Frost and Tchertkov, 2002;Hammett et al, 1999;Mahon, 1996;Saum et al, 1995;Struckman-Johnson et al, 1996;Taylor et al, 1995). Drug injection in prison was reported by more than one fifth of Russian prisoners who had ever injected a drug (Frost and Tchertkov, 2002), and by more than one third of Spanish female injecting drug 1 National Development and Research Institutes, Inc., 71 West 23rd Street, New York 10010.…”
Section: Introductionmentioning
confidence: 95%
“…2 Universidad Central Del Caribe, Centro de Estudios en Adiccion, Bayamón Puerto Rico. 3 Correspondence should be directed to Sung-Yeon Kang, PhD, National Development and Research Institutes, Inc., 71 West 23rd Street, 8th Floor, New York 10010;e-mail: kang@ndri.org. users who had ever been imprisoned (Estébanez et al, 2002). The proportion of consensual homosexual relations in prisons was estimated as 25% of inmate population in US midwestern prisons by correctional officers (Eigenberg, 2000), and 21% of the inmates in the same areas reported at least one episode of sexual coercion (Struckman-Johnson and Struckman-Johnson, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The association between incarceration and behaviours that increase the risk of HIV transmission among incarcerated IDU have been reported in a number of jurisdictions [32][33][34] . In the present study, MMT was associated with a reduction in incarceration, demonstrated by the strong negative association we observed between being on MMT and being incarcerated among study participants.…”
Section: Discussionmentioning
confidence: 99%